Primary pulmonary neoplasms in children: A report of five cases - Subhalakshmi Sengupta; Uttara Chatterjee; Ranjana Bandyopadhyay; Kuntal Bhowmick; Sugata Banerjee (Indian Journal of Medical and Paediatric Oncology)
Primary pulmonary neoplasms are uncommon in children and represent a wide spectrum of pathology from benign to malignant. They are quite different in their histopathologic distribution from that of adults. This study was done to analyze the histopathologic spectrum of primary lung tumors in children. All the resected specimens of lung in children over a period of 5 years were studied and only the cases of primary pulmonary neoplasms were further analyzed. There were two cases of inflammatory myofibroblastic tumor. The patients were boys aged 10 and 12 years, respectively. One case of bronchial carcinoid was diagnosed in a boy of 12 years. There were one case each of pleuropulmonary blastoma (PPB) in a girl of 9 years and pulmonary blastoma (PB) in a girl of 2 years of age. In our study, the two cases of inflammatory myofibroblastic tumor had excellent prognosis. However, the cases of PPB and PB were both associated with poor clinical outcome, whereas the case of bronchial carcinoid has been doing well on follow-up.